2005
DOI: 10.1002/bit.20566
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of tetracycline‐responsive recombinant protein production and effect on cell growth and ER stress in mammalian cells

Abstract: The inducible T-REx system and other inducible expression systems have been developed in order to control the expression levels of recombinant protein in mammalian cells. In order to study the effects of heterologous protein expression on mammalian host behavior, the gene for recombinant Human transferrin (hTf) was integrated into HEK-293 cells and expressed under the control of the T-REx inducible technology (293-TetR-Hyg-hTf) or using a constitutive promoter (293-CMV-hTf). A number of inducible clones with v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 36 publications
1
30
0
Order By: Relevance
“…Proteomic analysis of antibody-producing NS0 myeloma cells with varying productivity revealed a positive correlation between specific antibody productivity and the expression levels of ER chaperones like BiP and endoplasmin, and protein disulfide isomerase (PDI) (Smales et al, 2004). Similarly, a human embryonic kidney cell line, HEK-293, expressing high levels of transferrin was found to have elevated expression of BiP (Jones et al, 2005). These observations demonstrate that high-level production of recombinant proteins associates with up-regulation of the ER proteins involved in protein secretion.…”
Section: Introductionmentioning
confidence: 99%
“…Proteomic analysis of antibody-producing NS0 myeloma cells with varying productivity revealed a positive correlation between specific antibody productivity and the expression levels of ER chaperones like BiP and endoplasmin, and protein disulfide isomerase (PDI) (Smales et al, 2004). Similarly, a human embryonic kidney cell line, HEK-293, expressing high levels of transferrin was found to have elevated expression of BiP (Jones et al, 2005). These observations demonstrate that high-level production of recombinant proteins associates with up-regulation of the ER proteins involved in protein secretion.…”
Section: Introductionmentioning
confidence: 99%
“…Further, intracellular aggregation (Hasemann and Capra 1990;Hsu and Betenbaugh 1997;Hsu et al 1996;Hsu et al 1994;Schröder et al 2002), association of heterologous proteins with the molecular chaperone BiP/GRP78 (Dorner et al 1987;Hurtley et al 1989;Jarvis and Summers 1989;Kaufman et al 1988;Machamer et al 1990;Suzuki et al 1991), and dilation of the ER (Dorner et al 1989;Gennaro et al 1991) have been reported. BiP induction, a hallmark of ER stress and UPR activation, has been reported for many expression systems (Alete et al 2005;Downham et al 1996;Jones et al 2005;Miura et al 2001;Smales et al 2004). Further, even in secretory cell types such as plasma cells activation of the UPR has been observed (van Anken et al 2003;Zhang et al 2005).…”
Section: Introductionmentioning
confidence: 92%
“…Induction of BiP in several expression systems (Alete et al 2005;Dorner et al 1989;Downham et al 1996;Jones et al 2005;Miura et al 2001;Smales et al 2004;Watowich et al 1991), of NF-jB in human IL-6 expressing CHO cells (Teruya et al 2005), and of genes involved in the ER stress response including BiP, GRP94, calnexin, and HERP in human bone morphogenic protein 2 expressing CHO DUKX cells (Doolan et al 2008) demonstrates that the UPR is activated in many heterologous expression systems. Cooperativity of molecular chaperones and foldases may necessitate increasing expression of several chaperones simultaneously to reproducibly increase productivities.…”
Section: Engineering Of the Uprmentioning
confidence: 99%
“…The increased expression level of the P301L tau compared with that of WT tau most likely was due to stochastic differences in transfection efficiency. Previous work using this system to express human transferrin has shown that the transfection generates expression clones with a wide range of expression levels (Jones et al, 2005).…”
Section: Overexpression Of Wt and P301l Tau Did Not Induce The Uprmentioning
confidence: 99%
“…The increased expression level of the P301L tau compared with that of WT tau most likely was due to stochastic differences in transfection efficiency. Previous work using this system to express human transferrin has shown that the transfection generates expression clones with a wide range of expression levels (Jones et al, 2005).Once expression of tau was confirmed, cell samples were tested for UPR activation. Figure 6 shows splicing of XBP1 mRNA with a positive control from treatment of SH-SY5Y cells with TG for 1 hr.…”
mentioning
confidence: 99%